2021
DOI: 10.1016/j.theriogenology.2020.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bovine blastocysts indicates ovarian stimulation does not induce chromosome errors, nor discordance between inner-cell mass and trophectoderm lineages

Abstract: Contemporary systems for oocyte retrieval and culture of both cattle and human embryos are suboptimal with respect to pregnancy outcomes following transfer. In humans, chromosome abnormalities are the leading cause of early pregnancy loss in assisted reproduction. Consequently, pre-implantation genetic testing for aneuploidy (PGT-A) is widespread and there is considerable interest in its application to identify suitable cattle IVP embryos for transfer. Here we report on the nature and extent of chromosomal abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 72 publications
3
20
1
Order By: Relevance
“…This is due to the fact that this database only contains embryos pre-selected under strict morphological criteria by their breeder to maximise embryo biopsy survival, cryosurvival, and later live birth rates. Indeed, a link between embryo morphology and aneuploidy incidence has already been demonstrated [11,24], and this association is supported in our present work, especially for embryos biopsied at earlier developmental stages. Nonetheless, our findings strongly suggest an added benefit for PGT-A in addition to morphology screening in IVP, as we have shown that chromosomally abnormal embryos are still able to achieve the highest morphology scores.…”
Section: Relationship Between Chromosomal Abnormality and Embryo Morphologysupporting
confidence: 89%
See 3 more Smart Citations
“…This is due to the fact that this database only contains embryos pre-selected under strict morphological criteria by their breeder to maximise embryo biopsy survival, cryosurvival, and later live birth rates. Indeed, a link between embryo morphology and aneuploidy incidence has already been demonstrated [11,24], and this association is supported in our present work, especially for embryos biopsied at earlier developmental stages. Nonetheless, our findings strongly suggest an added benefit for PGT-A in addition to morphology screening in IVP, as we have shown that chromosomally abnormal embryos are still able to achieve the highest morphology scores.…”
Section: Relationship Between Chromosomal Abnormality and Embryo Morphologysupporting
confidence: 89%
“…The overall incidence of chromosome abnormalities detected in this study (14.1%) is considerably lower than previously reported in cattle (30% and higher, [9][10][11]). However, we suggest this lower figure is actually a substantial underestimation of the true overall incidence of chromosomal abnormalities following bovine IVP.…”
Section: Relationship Between Chromosomal Abnormality and Embryo Morphologycontrasting
confidence: 88%
See 2 more Smart Citations
“…Supplementary Materials: Supplementary Materials can be found at https://www.mdpi.com/1422 -0067/22/4/1838/s1 [82,83].…”
Section: Statistical Analysesmentioning
confidence: 99%